Physical Therapy Modalities and Rehabilitation Techniques in the Management of Neuropathic Pain - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
Neuropathic pain is an important problem because of its complex natural history, unclear etiology, and poor response to standard physical therapy agents. It causes severe disability unrelated to its etiology. The primary goals of the management of neuropathic pain are to detect the underlying cause, to define the differential diagnosis and eliminate risk factors, and to reduce the pain. The physician should also know the functional and psychologic conditions of the patient. Therefore, a multimodal management plan in neuropathic pain is essential. This review aimed to reflect a diverse point of view about various physical therapy modalities and rehabilitation techniques. Physical therapy modalities and rehabilitation techniques are important options and must be considered when pharmacotherapy alone is not sufficient. In addition, psychosocial support and cognitive behavioral therapy could also be taken into consideration. It has been suggested that the importance of pain rehabilitation techniques will increase in time and these will take a larger part in the management of neuropathic pain. However, it is now early to comment on these methods because of the lack of adequate publications.
Keywords: Neuropathic Pain; Management; Physical Therapy Modalities; Rehabilitation Techniques; COMPLEX REGIONAL PAIN; GRADED MOTOR IMAGERY; DIABETIC PERIPHERAL NEUROPATHY; ELECTRICAL NERVE-STIMULATION; MIRROR THERAPY; EFNS GUIDELINES; LASER; ELECTROTHERAPY; AMELIORATION; RECOVERY